(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Education is a key to reducing poverty in the medium and long term and one of the most important elements in national development, because with education for the community to be promising people more advanced in his thinking. Thought developed societies to form a Human Resources (HR) of high quality. in the District of Siau Tagulandang Biaro of school age who have not been able to get an education, in junior high school education who do not finish school amounted to 51 students from the data taken at the Department of Education Youth and Sports District Siau Tagulandang Biaro. The cause of the children who dropped out of school As well as some elementary school and junior high school in the district of Siau Tagulandang Biaro still not being prasyrarat terselenggaraya education among others damaged classrooms and the uneven ketersebaran teachers is a problem facing education in the District Siau Taguladang Biaro. Conditions as described previously prompted the authors to determine the depth on the performance of the Department of Education, Youth and Sports District Siau Tagulandang Biaro in implementing the nine-year compulsory education program. From the results of research and analysis concluded that the Performance Department of Education Youth and Sport in the Nine-Year Compulsory Education Program which terihat on five aspects, namely. Productivity, quality of service, responsiveness, responsibility and accountability. Of the five aspects of the new aspects that have good responsiveness in responding to community needs its citizens basic education, especially primary school dropouts and facilitate the higher education level, and an increase in APM elementary and junior high school through the nine-year compulsory education program Keywords: Performance, Organizational Performance, nine-year compulsory education